Body image perception and its relationship with the nutritional status of female adolescents - Souza, Emilly Rosa de (2022)
Body image has become a constant concern for society, given that the general population increasingly seeks physical improvement. However, adolescence is a period in which there is a greater search for the aesthetic standard, as it is a phase in which individuals experience the process of dealing with the physical and psychological changes caused by puberty, which can affect the perception of the image. body, especially among female adolescents. Objective: To analyze the scientific literature regarding the perception of body image and its relationship with the nutritional status of female adolescents. Materials and Methods: An integrative literature review was carried out, where articles were searched in the electronic databases: Google Scholar, Virtual Health Library (BVS), PubMed and Scielo, between the years 1999 to 2021, in Portuguese and English. Results: Data collection enabled the selection of 12 articles that followed the narrative in two areas: Body image perception of female adolescents; Relationship between nutritional status and body image perception. Final considerations: This study demonstrated the prevalence of body image dissatisfaction and distortion in female adolescents, and this dissatisfaction was observed mainly in overweight individuals, however, there were still those who had BMI within the ideal parameters that they stated feel dissatisfied with their body pattern. In this sense, the importance of interdisciplinary interventions between health and education professionals for parents and adolescents is highlighted.